INTEGRATIVE APPROACH TO CREATING THE STRUCTURE AND CONTENT OF THE CHEMISTRY TEACHING METHODOLOGY COURSE - Nishonov, Mirkozimjon (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2023)
Abstract This article describes in detail the importance and integration of chemistry, pedagogy, and psychology in determining the structure and content of the chemistry teaching methodology course. Based on the integrative approach, the process of creating a new pedagogical science of chemistry teaching methodology is based on the theoretical aspect.